Data Sharing: An Analysis of Medical Faculty Journals and Articles. Issue 1 (2nd January 2021) - Wiley, Chris
ABSTRACT: An increasing number of journals and publishers have data-sharing policies and data availability statements. This study examines data-sharing policies of faulty affiliated in medicine. More so, it addresses the following research questions: (1) What are the data-sharing policies of these research journals, (2) What is the relationship between data sharing, open access and journal impactor? and (3) What are current journal articles' applicability to Findable, Accessible, Interoperable and Reusable (FAIR) Sharing Principles. The data identified and examined in this study are retrieved from a visualization tool detailing authors, coauthors, articles, number of citations, grants that used visualization mapping to indicate the impact of research groups. This results in an analysis of sixty articles. Twenty-three percent of the journals have no research data policy, seventeen percent have strong data policies and sixty percent have policies that encourage research data sharing. Seventy-two percent of the journals are open access. All the articles are Findable, and a majority are accessible. There were challenges accessing articles' applicability to Interoperability and the results of reusability were inconclusive. Overall, data-sharing policies vary, no correlation between high impact factor and research data policies. Publishers with supportive data-sharing statements and journals with no policies create complexities in interpretation and application of data sharing. FAIR Sharing has mostly been implemented in the context of curated data more research is needed in its applicability to article data.